Bicarbonate-induced redox tuning in Photosystem II for regulation and protection - Rutherford,AW; Fantuzzi,A; Brinkert,K; De,Causmaecker; Kreiger-Liszkay,A (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The midpoint potential (Em) of QA/Q−AQA/QA−•, the one-electron acceptor quinone of Photosystem II (PSII), provides the thermodynamic reference for calibrating PSII bioenergetics. Uncertainty exists in the literature, with two values differing by ∼80 mV. Here, we have resolved this discrepancy by using spectroelectrochemistry on plant PSII-enriched membranes. Removal of bicarbonate (HCO3−) shifts the Em from ∼−145 mV to −70 mV. The higher values reported earlier are attributed to the loss of HCO3− during the titrations (pH 6.5, stirred under argon gassing). These findings mean that HCO3− binds less strongly when QA−• is present. Light-induced QA−• formation triggered HCO3− loss as manifest by the slowed electron transfer and the upshift in the Em of QA. HCO3−-depleted PSII also showed diminished light-induced 1O2 formation. This finding is consistent with a model in which the increase in the Em of QA/Q−AQA/QA−• promotes safe, direct P+Q−AP+•QA−• charge recombination at the expense of the damaging back-reaction route that involves chlorophyll triplet-mediated 1O2 formation [Johnson GN, et al. (1995) Biochim Biophys Acta 1229:202–207]. These findings provide a redox tuning mechanism, in which the interdependence of the redox state of QA and the binding by HCO3− regulates and protects PSII. The potential for a sink (CO2) to source (PSII) feedback mechanism is discussed.